Analysis of the Dairy Milk Supply Chain at Sapi Juara Farm, Bogor Regency - Rizki Yuda Musidi; Mutiara Azzahra; Desri YN Damanik; Ranjani Nuralifah; Eka Rindah Yani; Khoirul Aziz Husyairi; Tina Nur Ainun (International Journal of Economics, Management and Accounting, 2024)
Pamijahan District in Bogor Regency, West Java, is known as one of the main sources of milk supply for dairy cows in the region. Dairy cow's milk is a product that has high and stable demand and selling value. Supply Chain Management (SCM) at Sapi Juara Farm in Pamijahan District involves the distribution of dairy cow's milk which includes product flow, information and finance. This study aims to understand the SCM of dairy milk at Sapi Juara Farm, including product flow, information and finance, as well as efficiency as measured through marketing margin and farmer's share. This research uses quantitative descriptive methods with primary data obtained from interviews. The results of the analysis show that there is a flow of dairy milk products, a flow of information from farmers to various actors in the supply chain, and a flow of funds that includes costs and profits from nine distribution channels that influence the performance of the supply chain based on the payment system. From the analysis of the profit share value, it can be seen that the SCM for dairy cow milk in Pamijahan District is running efficiently. It is hoped that SCM in Pamijahan District can be more efficient to avoid losses at each stage or link in the chain and stabilize milk prices in the market, while improving the welfare of farmers, especially at Sapi Juara Farm.